2021
DOI: 10.4025/actascianimsci.v44i1.53445
|View full text |Cite
|
Sign up to set email alerts
|

Weaning and concentrate supplementation on the characteristics of carcass cuts and longissimus muscle of Suffolk lambs finished on pasture

Abstract: The aim of this study was to evaluate the influence of weaning and concentrate supplementation on the characteristics of carcass cuts and longissimus muscle of Suffolk lambs finished on a Tifton 85 (Cynodon spp.) pasture. Weaning and concentrate supplementation strategies were evaluated in four finishing systems: i) non-weaned and non-supplemented lambs; ii) non-weaned lambs supplemented with concentrate in creep feeding; iii) weaned and non-supplemented lambs; and iv) weaned lambs supplemented with concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…These are influenced by the animal's age, weight, breed, sex, nutritional status ( 73 , 74 ), and production system. The weight and yield of carcasses are significant determinants of commercial value with better returns ( 75 ). The mean tissue content of the leg showed that the muscles had the greatest contribution (66.70%), followed by bone (18.89%) and fat (10.09%) ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…These are influenced by the animal's age, weight, breed, sex, nutritional status ( 73 , 74 ), and production system. The weight and yield of carcasses are significant determinants of commercial value with better returns ( 75 ). The mean tissue content of the leg showed that the muscles had the greatest contribution (66.70%), followed by bone (18.89%) and fat (10.09%) ( 76 ).…”
Section: Discussionmentioning
confidence: 99%